UPAYA MENINGKATKAN KEMAMPUAN BERCERITA MELALUI PEMANFAATAN MEDIA PANGGUNG BONEKA PADA ANAK USIA 5-6 TAHUN - Titi Suhaeti, Ayu Fajarwati, Iman Sampurna (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
This study aims to determine whether there is an increase in storytelling ability in children aged 5-6 years at Al  Muhajirin Kindergarten, Tunjung Teja Subdistrict through the use of puppet stages and to find out how the use of  puppet stages in an effort to improve storytelling ability in children aged 5-6 years at Al Muhajirin Kindergarten,  Tunjung Teja Subdistrict. The population in this study included all students aged 5-6 years at Al Muhajirin  Kindergarten as many as 13 students. With data collection techniques using oral tests and interviews. The results of this  study indicate that the storytelling ability of children aged 5-6 years at Al Muhajirin Kindergarten, Tunjung Teja  District has increased after using puppet stage media. In Cycle I, learning outcomes showed a number of children in the  developing category, with total achievement increasing from before the action. However, these results have not met the  specified criteria, so improvements are needed in Cycle II. In Cycle II, the observation results showed further  improvement, with a good achievement category.